Pengembangan E-Modul Berbasis Flipbook Maker pada Kursus Perawatan Tangan, Kaki dan Kuku - Anisa Taqwina; Rahmiati; Linda Rosalina; Refdinal (Journal for Lesson and Learning Studies, 2022)
The learning objectives of hand, foot and nail care for students of makeup and beauty education is not sufficient and not optimal. Therefore, there is a need for innovation in learning, especially hand care and foot care learning materials. ICT-based modul is solution to overcome this problem. This study aims to develop e-module learning media based on flipbook maker in the department of cosmetology and beauty. The methodology used is Research and Development (R&D) with the Four D procedure through the stages of define, design, develop and disseminate. The research subjects were 3 media experts and 3 material experts. While the research subjects in the practical test were 2 lecturers and 20 students of the department of cosmetology and beauty. Data were obtained by using test instruments to test the effectiveness and non-test instruments to test the validity and practicality of the research process. Data analysis uses V Aiken calculations for product validation, percentage formulas for practicality and effectiveness. The results of this research show there is a significant comparison of students' understanding of hand, foot and nail care using flipbook maker-based e-module learning media. Based on all these analyzes it was concluded that the e-module based on flipbook maker was stated to be valid, practical and effective as one of the learning media for the hand, foot and nail care course.